Modulating electron injection from an organic dye to a titania nanoparticle with a photochromic energy transfer acceptor. Issue 26 (7th June 2016) - Vamvounis, George; Glasson, Christopher R.; Bieske, Evan J.; Dryza, Viktoras
Abstract : A diarylethene molecular switch has been used within an energy transfer scheme to affect the electron injection efficiency of an organic dye sensitiser attached to a titania nanoparticle. Abstract : We have prepared titania nanoparticles with an organic dye sensitiser and diarylethene molecular switch attached to the surface. Spectroscopic investigations show that the dye sensitiser's electron injection efficiency is reduced when the diarylethene is switched from its colourless, ring-open isomer to its coloured, ring-closed isomer, due to the introduction of a competing energy transfer pathway.